The Prognostic Value of CD133 in Predicting the Relapse and Recurrence Pattern of High-Grade Gliomas on MRI: A Meta-Analysis - Abdoli Shadbad, Mahdi; Hosseinkhani, Negar; Asadzadeh, Zahra; Brunetti, Oronzo; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Oncology, 2021)
Background Cancer stem cells have been implicated in tumor relapse, tumor invasion, and cancer therapy resistance in high-grade gliomas; thus, characterizing cancer stem cell-related markers can help determine the prognosis of affected patients. Preclinical studies have reported that CD133 is implicated in tumor recurrence and cancer therapy resistance in high-grade gliomas; however, clinical studies have reported inconclusive results regarding its prognostic value in patients with high-grade gliomas. Methods We systematically searched the PubMed, Scopus, Web of Science, and Embase databases to obtain peer-reviewed studies published before March 10, 2021. Then, we conducted the current systematic review and meta-analysis based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statements. By applying the random-effect model, the effect size of studies investigating the progression-free survival (PFS), time to local recurrence (TTL), and time to distant recurrence (TTD) were calculated using RevMan version 5.4. The heterogeneity between the included studies was studied by the I2 index and Cochran’s Q test. Egger test was performed on funnel plots to investigate the potential asymmetry and publication bias among the included studies using CMA version 2. Results With the 10% cut-off, CD133 protein overexpression is associated with the inferior PFS of patients with high-grade gliomas. Increased CD133 protein expression is associated with sooner distant tumor recurrence on MRI in glioblastoma patients and patients with high-grade gliomas and improved TTL on MRI in glioblastoma patients. Conclusion Based on the current evidence from 1086 patients with high-grade gliomas, CD133 overexpression is a valuable marker to predict tumor relapse and tumor recurrence patterns in patients with high-grade gliomas.